Hydroxyl group-directed, tartaric acid-catalyzed synthesis of meta-functionalized aryl ethers and phenols through domino conjugate addition/aromatization of para-quinols. Issue 24 (12th October 2021) - Chen, Guo-Shu; Li, Jia-Hui; Chen, Shu-Jie; Lin, Wen-Xia; Ren, Hai; Deng, Dong-Sheng; Liu, Yun-Lin
Abstract : A tartaric acid-catalyzed three-component reaction of para -quinols, organoboronic acids, and alcohols affords meta -alkenylated aryl alkyl ether in good yields. In the absence of alcohols, meta -functionalized phenols could be obtained selectively. Abstract : A tartaric acid-catalyzed three-component reaction of para -quinols, organoboronic acids, and alcohols is reported, leading to meta -alkenylated aryl alkyl ether in a single step. Moreover, meta -functionalized phenols could also be obtained in the absence of alcohols. Initial mechanistic studies indicated that the free hydroxy group of p -quinol plays a vital role in initiating the conjugate addition.